Modified Snakes and Ladders to Increase Elementary Students Knowledge About Anticipating Child Sexual Abuse - Widyastuti, Yani; Setiani, Ariana; Eka, Yuliasti; Wulandari, Diah (Fakultas Kedokteran UPN Veteran Jakarta Kerja Sama KNPT, 2024)
One in four girls and one in 13 boys globally experience child sexual abuse (CSA), a public health crisis. Snakes and ladders-based reproductive health education to combat CSA. This study examined the impact of snakes and ladders game modification on CSA anticipation knowledge. The study was quasi-experimental with pre- and post-test control groups. Sample size was 118. The experimental group received a modified snakes and ladders game comprising 59 students, whereas the control group received a brochure. The sampling method is sequential. This study included grade 4-6 primary pupils. The snakes and ladders modification group averaged pretest 68.3 SD 16.4 and posttest 82.0 SD 12.5. The leaflet group averaged 67.8 SD 11.4 pre-test and 76.4 SD 14.1 post-test. The snake and ladder modification group increased 13.6 and the leaflet group 8.5. An average difference of 5.1 was found between the snakes and ladders modification group and the leaflet, with a p-value of 0.037 < It can be concluded that snake modification increases female students' average knowledge.